(untitled) (TAMADDUN NURI JURNALI, 2025)
This study demonstrates the close interrelation between visual perception and cognitive processes in Turkish verbal expressions, highlighting the critical role of language as a connecting link between sensory experience and mental processing, thus ensuring effective communication.